Draft Guidelines for the Allocation of Public Logistics Centres of International Importance - Ondrej Stopka; Rudolf Kampf; Jiri Kolar; Iveta Kubasakova; Christopher Savage (Communications - Scientific letters of the University of Zilina, 2014)
This paper deals with the design of methodology for the allocation of public logistics centres (VLC) of international importance in the Slovak Republic. The decision on the location of the logistics centre can be seen as a decision problem; for this type of task the multi-criteria analysis method is used. The first part of the paper (except introduction) includes a description of the general procedure for multi-criteria assessment of the variants. The second part presents the identification of the variants and the establishment of the evaluation criteria. The third part of the paper provides an identification of appropriate methods for a given type of task. The last part of the contribution presents the creation of a criteria matrix and the determination of prioritizing variants using the method of weighted sum, the weights being determined on the basis of Saaty‘s pairwise comparison method.